Pengaruh Bio Slurry Cair terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Maulidi Triansyah Puja Anugrah; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to examine the effect of liquid bio-slurry and get the best dose on the growth and yield of the pakcoy (Brassica rapa L.) plant. The experiment was conducted at Experimental Garden of Agriculture Faculty of Riau University, Campus Bina Widya km 12,5 Simpang Baru Village Tampan Sub District, Pekanbaru. This research was conducted for 2 months, from August to September 2017. The research was conducted experimentally using Randomized Complete Design (RAL). The practice is liquid bio-slurry (B) comprising five levels with doses: B0 = Without liquid bio-slurry, B1 = 2 liters of liquid bio-slurry.m-2, B2 = 4 liters of liquid bio-lurry.m- 2, B3 = 6 liters of liquid bio-slurry.m-2, B4 = 8 liters of liquid bio-slurry.m-2. Each treatment was repeated four times so that there were 20 experimental units. The observational data were analyzed statistically by using Analysis of Varian SAS 9.1 untuk windows,then continued with BNT test at 5% level. The observed parameters consist of plant height, leaf number, leaf area, fresh weight of plant per m2, consumption weight per m2. The results showed that the provision of liquid bio-slurry can increase the growth and yield of the pakcoy plant at a dose of 6 l.m-2 gives the best results on the growth and yield of the pakcoy plant. Keywords: Liquid Bio Slurry and Pakcoy